2020
DOI: 10.1515/cclm-2020-0626
|View full text |Cite
|
Sign up to set email alerts
|

A biological profile for diagnosis and outcome of COVID-19 patients

Abstract: ObjectivesAs severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) pandemic is increasing its victims on a global scale with recurring outbreaks, it remains of outmost importance to rapidly identify people requiring an intensive care unit (ICU) hospitalization. The aim of this study was to identify Coronavirus Disease 2019 (COVID-19) biomarkers, to investigate their correlation with disease severity and to evaluate their usefulness for follow-up.MethodsFifty patients diagnosed with SARS-Cov-2 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…Lymphopenia was also found to be an early predictor of mortality, consistent with literature review ( 22 , 23 ). We found that in non-survivors, lymphocyte count is lower early in admission, and continues to trend downwards during the hospitalization.…”
Section: Discussionsupporting
confidence: 88%
“…Lymphopenia was also found to be an early predictor of mortality, consistent with literature review ( 22 , 23 ). We found that in non-survivors, lymphocyte count is lower early in admission, and continues to trend downwards during the hospitalization.…”
Section: Discussionsupporting
confidence: 88%
“…Besides the obvious contribution of diagnosis through RT-PCR, there was also the contribution to patient management and risk stratification for COVID-19 patients through the use of commonly requested test panels such as full blood counts, renal, liver and bone profiles. Testing for additional hyper-inflammatory, cardiac and haemostasis biomarkers [8,[10][11][12][13] was also implemented (or existing capacity increased, where these tests were already available).…”
Section: Discussionmentioning
confidence: 99%
“…During this time, the development of an expanded spectrum of laboratory tests for patients with confirmed or suspected COVID-19 was completed in Irish laboratories [7,8]. This was done while maintaining essential testing requirements, in the face of expanding health and safety requirements to ensure the protection of members of staff.…”
Section: Introductionmentioning
confidence: 99%
“…The neoepitope technology for the systemic assessment of ECM turnover as a measure of organ fibrosis has previously been described [25,26]. This technology utilizes monoclonal antibodies to detect the generation of newly formed epitopes of collagens and other ECM proteins released during inflammation and fibrosis progression as well as markers of wound healing that can reflect a disturbed coagulation [25,31,36]. The neoepitope technology allows for the detection of both fibrogenesis [32] and fibrolysis of up to twenty-eight different collagens, each contributing to the integrity and quality of the ECM in different organs, including the lungs [26].…”
Section: Markers Of Lung Extracellular Matrix Remodelling Used To Evamentioning
confidence: 99%
“…Potentially, markers of ECM remodelling, as [25,26] described here may be used to predict outcome, event at an earlier time point, nevertheless this is speculations. Furthermore, the kinetics of routine clinical markers was followed in fifty patients diagnosed with COVID-19, and admitted to the hospital [36]. Patients were followed during hospitalization and one month prior to discharged, as well as stratified into non-ICU and ICU severity.…”
Section: Routine Clinical Parameters As Markers Of Outcome In Covid-19mentioning
confidence: 99%